Patient-centered care and patient satisfaction: Validating the patient-professional interaction questionnaire in China - Tao Han; Sisi Li; Xueyuan Li; Chenhao Yu; Jiahui Li; Tiantian Jing; Mayangzong Bai; Yue Fang; Kun Qian; Xiaoyan Li; Xiaoyan Li; Huigang Liang; et al. (Frontiers in Public Health, 2022)
ObjectiveTo introduce patient-centered approach in China and to relate it with Chinese patient satisfaction via validating the Chinese version of Patient-Professional Interaction Questionnaire (PPIQ-C).DesignThis cross-sectional survey was conducted through face-to-face interviews from June to September in 2019. Participants rated their patient-centered care experience via the 16-item translated PPIQ, their experience of the received medical service, and their overall satisfaction.SettingKunshan Huaqiao People's Hospital in Jiangsu, China.ParticipantsA total of 230 participants (87 males and 143 females; 108 outpatients and 122 inpatients).ResultsPPIQ-C exhibited acceptable psychometric properties. Data revealed a single factor model of the 16 PPIQ-C items [χ(4)2 = 12.394, p = 0.823, CFI = 1.000, TLI = 1.019, RMSEA = 0.000, SRMR = 0.032] had a superior model fit over the original first-order with four correlated factors and the second-order structures. The overall reliability was excellent (McDonald's ω = 0.975). In terms of patient satisfaction, process, treatment quality, and communication significantly predicted patient satisfaction, while environment, staff attitude, and medical ethics did not [R2 = 0.427, F(6) = 24.887, p < 0.001]. Most importantly, the total score of PPIQ-C predicted patient satisfaction above and beyond the above-mentioned medical service perspectives (B = 0.595, SE = 0.207, p = 0.004). Finally, the constructive effect of PCC on patient satisfaction was stronger for departments of Pediatrics than Surgery.ConclusionsThe Chinese version of the PPIQ scale (PPIQ-C) exhibited acceptable psychometric properties. Yet the distinction among the four factors was not supported, suggesting potential difference(s) across cultures. Patient-centered care (PCC), reflected by the overall PPIQ-C score, predicted overall patient satisfaction above and beyond other medical service perspectives. Adopting PCC approach in appropriate situations will probably advance the development of performance evaluation systems in China, thus improving the overall health care and patient satisfaction.